Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/jgm.2672
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral small hairpin RNA delivery reduces apical sodium channel activity in differentiated human airway epithelial cells

Abstract: We have established a generic method for studying the effect of RNA interference in HBEC-ALI using standard lentiviral vectors. Down-regulation of ENaCα by lentiviral shRNA expression vectors as shown in the absence off-target effects has potential therapeutic value in the treatment of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
(73 reference statements)
2
14
0
Order By: Relevance
“… 13 Finally, an shRNA approach following lentiviral transduction of immortalised and primary cell lines used αENaC as their target. 12 The authors transduced primary cells before the formation of tight junctions, unlike our fully differentiated cell approach, and showed up to 60% silencing. Similar to our findings, they have shown that reducing mRNA results in proportional changes in the short circuit current responses and also reduced net apical to basal fluid flux.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 13 Finally, an shRNA approach following lentiviral transduction of immortalised and primary cell lines used αENaC as their target. 12 The authors transduced primary cells before the formation of tight junctions, unlike our fully differentiated cell approach, and showed up to 60% silencing. Similar to our findings, they have shown that reducing mRNA results in proportional changes in the short circuit current responses and also reduced net apical to basal fluid flux.…”
Section: Discussionmentioning
confidence: 98%
“… 11 Silencing of ENaC expression, by short interfering RNA (siRNA)-mediated RNA interference, offers a more promising therapeutic route. 12–14 Potential advantages of nanoparticle-mediated siRNA therapy include its potency, specificity, duration 15 and restriction to the airways to prevent nephrotoxicity. Transfection of the CF airway epithelium requires protection of siRNA from nucleases, penetration of the mucus and periciliary liquid layer (PCL) and targeted uptake by the epithelial cells 16 with purpose-designed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The self-inactivating pRRLsin18.cPPT.CMV.eGFP.Wpre and pCCL.PPT.U1aENaCshRNA.hPGKΔNGFR.Wpre constructs were used to generate vesicular stomatitis virus (VSV)-pseudotyped LV stocks for green fluorescent protein (GFP)—LV–GFP and nerve growth factor receptor (NGFR) —LV–ΔNGFR, respectively—as previously described [14,15,16]. The viral titer was determined by HeLa cell (ATCC ® CCL-2™) infection and subsequent flow cytometry analysis, as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…Ten thousand cells were examined in each experiment. Analysis of ΔNGFR + cells was performed by plotting the R-PE channel (FLH-2) against the FLH-3 channel, as previously done [16]. For the evaluation of GFP expression in domes, cells were infected with LV–GFP at 2000 MOI preincubated with 2 μL of VM in presence of magnetic field for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular tools currently available to perform functional studies in fully differentiated ciliated bronchial epithelial cells are still very limited. However, silencing of PRRs using lentivirus-mediated short hairpin RNA (shRNA) transduction has been described without apparent artefactual activation of the innate immune responses [45], opening the path to studies of PRR function in this model. Although restricted to healthy adult volunteers, controlled human challenge studies, which consist of carefully monitored and controlled infection, are beginning to provide unique insights into RSV pathogenesis in humans [46].…”
Section: Prr Function: Moving From Experimental Models To Natural Hummentioning
confidence: 99%